2015
DOI: 10.1007/s12043-015-1078-5
|View full text |Cite
|
Sign up to set email alerts
|

Comments on: “Crystal growth and comparison of vibrational and thermal properties of semi-organic nonlinear optical materials”

Abstract: Gunasekaran et al (Pramana -J. Phys. 75 683-690 (2010)) report to have grown the nonlinear optical crystals urea thiourea mercuric chloride (UTHC) and urea thiourea mercuric sulphate (UTHS). We argue that UTHC and UTHS are dubious crystals and are not what the authors propose.Keywords: crystal growth; urea thiourea mercuric chloride; urea thiourea mercuric sulphate. CommentDuring the course of a literature survey of metal compounds containing both thiourea and urea ligands, the title paper by Gunasekaran et al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…[5], while the 1:3 compound [Cd(tu) 3 (SO 4 )] crystallizes in the centrosymmetric triclinic space group Pī having unit cell parameters a = 8.77(2), b = 9.05(2), c = 9.83(1) Å , a = 91.3(2)°, b = 111.9(1)°, c = 95.5(2)° [6]. Although these data appear the closest to the cell reported (without any esd values) in the title paper, UTCS should be declared as a dubious crystal in view of (1) the absence of structure refinement details, (2) non-reporting of any chemical composition, and (3) claim of using equimolar ratios of CdSO 4 and tu for crystal growth. For a dubious crystal (UTCS), studies such as thermal analysis and NLO property are meaningless and hence are not commented.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…[5], while the 1:3 compound [Cd(tu) 3 (SO 4 )] crystallizes in the centrosymmetric triclinic space group Pī having unit cell parameters a = 8.77(2), b = 9.05(2), c = 9.83(1) Å , a = 91.3(2)°, b = 111.9(1)°, c = 95.5(2)° [6]. Although these data appear the closest to the cell reported (without any esd values) in the title paper, UTCS should be declared as a dubious crystal in view of (1) the absence of structure refinement details, (2) non-reporting of any chemical composition, and (3) claim of using equimolar ratios of CdSO 4 and tu for crystal growth. For a dubious crystal (UTCS), studies such as thermal analysis and NLO property are meaningless and hence are not commented.…”
supporting
confidence: 51%
“…Based on the IR spectrum, it can be concluded that the name 'urea thiourea cadmium sulfate' is inappropriate for the UTCS crystal. The same criterion namely the absence of the C=O vibration was used as evidence to prove the dubious nature of five other improperly characterized compounds (Table 1) claimed to contain both urea and thiourea [2][3][4].…”
mentioning
confidence: 99%